2019
DOI: 10.1177/0263617419866986
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the isosteric heat of adsorption for supercritical methane on shale under high pressure

Abstract: The isosteric heat of adsorption (IHA) is one of the key thermodynamic variables for evaluating the interaction between shale and methane, which is rarely studied especially under high pressure. In this work, we conducted methane adsorption experiments at pressures up to 30 MPa and different temperatures on shale samples collected from Longmaxi formation in Sichuan Basin, China. Based on the definition of IHA and Langmuir adsorption model, we proposed a new method to analyze the IHA of methane on shale under f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
3
12
0
Order By: Relevance
“…Ji et al reported that pre-gas window shales had Q st values in the range 7.3-15.3 kJ mol −1 and a gas window shale was 18.4 kJ mol −1 [8]. These Q st values are similar to previously published values for carbon (9-24 kJ mol −1 ) [53][54][55], coal (10-22 kJ mol −1 ) [56] and shale (7-24 kJ mol −1 ) [8,[76][77][78].…”
Section: The Role Of Shale Structure and Kerogen Maturitysupporting
confidence: 80%
“…Ji et al reported that pre-gas window shales had Q st values in the range 7.3-15.3 kJ mol −1 and a gas window shale was 18.4 kJ mol −1 [8]. These Q st values are similar to previously published values for carbon (9-24 kJ mol −1 ) [53][54][55], coal (10-22 kJ mol −1 ) [56] and shale (7-24 kJ mol −1 ) [8,[76][77][78].…”
Section: The Role Of Shale Structure and Kerogen Maturitysupporting
confidence: 80%
“…As illustrated in Figure , these different types of micro-nanopores make up the complex storage spaces and flow channels in shale. Furthermore, the strong heterogeneity and anisotropy of the complex pore system with the intense fluid–solid interaction on the nanoscale cause ambiguity regarding shale gas transport characteristics and mechanisms. Therefore, the pore-size distribution, heterogeneity, and anisotropy of these microstructures are characterized and analyzed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to research into the relationship between isosteric enthalpy and adsorption capacity, some studies have held that there existed a positive correlation between isosteric enthalpy and adsorption capacity, while others believed the opposite, ,,,, considering that there was a negative correlation between the two. This was mainly caused by two reasons.…”
Section: Resultsmentioning
confidence: 99%
“…An analysis of the thermodynamic characteristics of methane adsorption in shale would contribute to an understanding of important information relating to the interaction between methane and shale. , Many researchers have focused on changes in thermodynamic potentials in the adsorption process, such as isosteric enthalpy and isosteric entropy, , ,, and conclusive results have been obtained. Nonetheless, two different opinions concerning the relationship between isosteric enthalpy and adsorption capacity exist, and a definitive explanation has not yet been formed.…”
Section: Introductionmentioning
confidence: 99%